Enhancing EFL Speaking Fluency and Confidence through ChatGPT Voice in Contextual Learning at Madrasah Aliyah - Nunung Yuliantini (Jurnal Iman dan Spiritualitas, 2026)
English-speaking fluency still constitutes a challenge for Indonesian students, especially owing to a lack of proper practice environments. To cater to the problem, a study was conducted to explore the effectiveness of the implementation of Contextual Teaching Learning (CTL) combined with ChatGPT Voice technology. Grounded on the tenets based on Vygotsky’s Social Development Theory, along with the principles of Communicative Language Teaching (CLT), the research paper explores a teaching approach incorporating AI-based scaffolding in linking theoretical foundations of education from the classrooms towards its application in practical contexts. The research undertaken for improvement used a classroom-based action research method on a sample population of 20 students of Grade XI from Madrasah Aliyah Subang. Findings drawn from quantifiable research showed a pronounced improvement in the mean scores of the students, from 68.2 to 83.5. Findings drawn from the qualitative approach showed lowered foreign language anxieties among students, along with improved levels of self-confidence owing to private, non-threatening AI-based interactions. Fluency in English speaking continues to be a problem for Indonesian learners, which is mainly because of a real-life application setting for enhanced proficiency. In an effort to create a setting where learning can take place, this paper tries to analyze a learning design using an application of contextual teaching through ChatGPT Voice technology. This paper uses a classroom research design for action analysis with a class of 20 grade XI students in Madrasah Aliyah Subang. This study found a significant increase in class mean scores, which improved from 68.2 to 83.5. In regard to the qualitative analysis, it can be determined that odds in a private setting with low stakes due to interaction with an artificial intelligence system reduced IIF (Indonesian International Friendship) language fluencies in class. Based on these analyses, it can be therefore determined that through a joint use of a contextual learning tool with an artificial intelligence system in an Indonesian class setting study, enhanced levels of proficiency can be achieved.